Portugal e Brasil em diálogo: um estudo da poesia simbolista de Camilo Pessanha e Maranhão Sobrinho à luz da literatura comparada - ARAÚJO, Samara Santos (2015)
The main objectives of this dissertation are to investigate the relationship between the Portuguese and the Brazilian Symbolist productions, represented respectively by the Portuguese poet Camilo Pessanha and by the Brazilian poet (from the State of Maranhão) Maranhão Sobrinho; to emphasize the importance of Comparative Literature for artistic and cultural study of a given society; and to rescue as well as spread the symbolist poetry of the State of Maranhão through its poet Maranhão Sobrinho. This dissertation also emphasizes the study of the major themes of Symbolism - time, avoidance (cosmic integration, cult of the past, drunkenness, sleep/dream and death), love and the female figure, exile, and Satanism -having the Theory of Comparative Literature as theoretical reference. Such theory will support the study of the convergent and divergent relationship between the poetry of those poets mentioned, starting from the thematologyand the basic concepts of Comparative Literature: influence, dialogue, interdiscursivity and intertextuality.